Cytotoxic effects of crotoxin from Crotalus durissus terrificus snake in canine mammary tumor cell lines - Pedro, Giovana [UNESP]; Brasileiro, Felipe César da Silva [UNESP]; Macedo, Jamile Mariano; Soares, Andreimar Martins; Mafra, Gabriel Caporale [UNESP]; Alves, Carlos Eduardo Fonseca [UNESP]; Laufer-Amorim, Renée [UNESP] (FapUNIFESP (SciELO), 2024)
Background: Mammary gland tumors are the most prevalent neoplasm in intact female dogs, and they are good natural models to study comparative oncology. Most canine mammary malignancies, as in women, are commonly refractory to conventional therapies and demand continuous new therapeutic approaches. Crotalus durissus terrificus, also called rattlesnake, has more than 60 different proteins in its venom with multiple pharmaceutical uses, such as antitumor, antiviral, and antimicrobial action. Crotoxin, a potent β-neurotoxin formed by the junction of two subunits, a basic subunit (CB-PLA2) and an acidic subunit (crotapotin), has already been reported to have anticancer properties in different types of cancers. Methods: In this work, we describe the cytotoxic potential of crotoxin and its subunits compared to doxorubicin (drug of choice) in two canine mammary carcinoma cell lines. Results: Crotoxin, CB-PLA2, crotalic venom, and doxorubicin decreased cell viability and the ability to migrate in a dose-dependent manner, and crotapotin did not present an antitumoral effect. For all compounds, the predominant cell death mechanism was apoptosis. In addition, crotoxin did not show toxicity in normal canine mammary gland cells. Conclusion: Therefore, this work showed that crotoxin and CB-PLA2 had cytotoxic activity, migration inhibition, and pro-apoptotic potential in canine mammary gland carcinoma cell lines, making their possible use in cancer research.
Keywords: Biological compounds; Comparative oncology; Crotalus durissus terrificus venom; Mammary tumor